Enhancing luminescent performance in spark plasma sintered YSZ/YAG multilayer ceramics through ultrasound processing; Ceramics International; Vol. 51, iss. 16, Pt. 1 - Paygin V. D. Vladimir Denisovich; Valiev D. T. Damir Talgatovich; Dvilis E. S. Edgar Sergeevich; Khasanov O. L. Oleg Leonidovich; Deulina D. E. Darjya Evgenjevna; Stepanov S. A. Sergey Aleksandrovich (2025, 2025)
This study investigates the synergistic effects of ultrasound treatment and spark plasma sintering (SPS) on the microstructure, sintering behavior, and luminescent properties of yttrium-stabilized zirconia (YSZ) and yttrium-aluminum garnet (YAG) co-doped with Ce3+ and Eu3+ multilayer ceramics. For the first time, two ultrasound methods suspension pretreatment and ultrasound pressing were integrated with SPS to fabricate functionally graded ceramics (FGCs). Ultrasound treatment suspension reduced the shrinkage onset temperature by ∼50 °C and enhanced ceramics consolidation, achieving a 9 % increase in relative shrinkage compared to conventional SPS. Ultrasound pressing further enhances the sintering process by reducing the temperature range for intense shrinkage and increasing the shrinkage value by 15 %. The ultrasound treatment improved photoluminescence (PL) efficiency in YSZ:1Ce/YAG:1Ce and YSZ:10Eu/YAG:1Ce ceramics by 2 and 7 %, respectively. The cathodoluminescence (CL) intensity increased 3-fold for ceramics using ultrasound pressing with SPS consolidation. These advancements highlight the potential combination of ultrasound-assisted and SPS method for producing high-performance luminescent multilayered ceramics with applications in optoelectronics